Cover Picture: On‐Surface Isomerization of Indigo within 1D Coordination Polymers (Angew. Chem. Int. Ed. 15/2024) - Xu, Hongxiang; Chakraborty, Ritam; Adak, Abhishek Kumar; Das, Arpan; Yang, Biao; Meier, Dennis; Riss, Alexander; Reichert, Joachim; Narasimhan, Shobhana; Barth, Johannes V.; Papageorgiou, Anthoula C. (Angewandte Chemie International Edition, 2024)
Indigo , an ancient, plant‐derived fabric dye, can be used to make Fe coordination polymers on silver surfaces as reported by Biao Yang, Joachim Reichert, Shobhana Narasimhan, Johannes V. Barth, Anthoula C. Papageorgiou et al. in their Research Article (e202319162). Within such coordination polymers on the close‐packed silver surface, thermally activated switches from trans to cis indigo are triggered and result in isomeric indigo‐Fe coordination polymers.